2015
DOI: 10.1039/c5cc00996k
|View full text |Cite
|
Sign up to set email alerts
|

A pyrazolate-stabilized sodium hydride complex

Abstract: The reaction of a sterically demanding sodium pyrazolate complex with n-butylsodium and diphenylsilane afforded the first well-defined molecular sodium hydride complex [(pz)6Na7H] (pz = 3,5-di-tert-butylpyrazolate) that could be structurally characterised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The sole example of a molecular sodium hydride was reported by Stasch in 2015 as an extension of his “bottom up” strategy which allowed the isolation of the lithium species 71 – 75 . The one-pot reaction of the sodium pyrazolate, [Na­(pz)] (pz = 3,5-di- tert -butyl­pyrazolate), with n BuNa and diphenylsilane at 90 °C for 2 h enabled the isolation of the sodium hydride species, [(pz) 6 Na 7 H] ( 82 ), in an impressive 65% yield.…”
Section: Molecular Hydrides Of the Group 1 Metalsmentioning
confidence: 99%
“…The sole example of a molecular sodium hydride was reported by Stasch in 2015 as an extension of his “bottom up” strategy which allowed the isolation of the lithium species 71 – 75 . The one-pot reaction of the sodium pyrazolate, [Na­(pz)] (pz = 3,5-di- tert -butyl­pyrazolate), with n BuNa and diphenylsilane at 90 °C for 2 h enabled the isolation of the sodium hydride species, [(pz) 6 Na 7 H] ( 82 ), in an impressive 65% yield.…”
Section: Molecular Hydrides Of the Group 1 Metalsmentioning
confidence: 99%
“…At 60 8C, it only reached 63 %after 12 h. Such low to moderate levels of conversion are mostp robably the outcome of the very poor solubility and partial passivation of commercial KH. [22] In addition, during ac ontrolled equimolar reactionb etween DippH with Ph 2 SiH 2 in the presence of one equivalent of [LiN(SiMe 3 ) 2 ]i n THF,t he complex [(THF) 2 Li{N(SiHPh 2 )(Dipp)}] (1)w as isolated in 87 %y ield. As depicted in Scheme 3, this lithium complexi sp resumably formed upon reaction of the monocoupled product M with ap utative lithium hydride [LiH] species such as that (III)p roposed as an intermediate in the mechanisms suggestedi n Scheme2.C omplex 1 was characterized in solution by 1 Ha nd 13 C{ 1 H} NMR, and its molecular solid-state structure was established by X-ray diffractiona nalysis ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“… We found that changing the reaction ratio from 2:3 to 1:1 affords a different sulfur-bridged structure in (Δ) 4 -Na 8 [Ag 4 {Rh­( l -cys) 3 } 4 ] (Na 8 [ 1 ]), which contains a tetrahedral {Ag 4 } 4+ core surrounded by four Δ-[Rh­( l -cys) 3 ] 3– units (Scheme ). Remarkably, the treatment of Na 8 [ 1 ] with NaBH 4 in a basic aqueous solution does not reduce the {Ag 4 } 4+ core but leads to the insertion of a hydride ion to produce (Δ) 4 -Na 9 [Ag 4 H­{Rh­( l -cys) 3 } 4 ] (Na 9 [ 2 ]) with an {Ag 4 H} 3+ core, which is unusually stable in aqueous media under ambient conditions; related main-group and transition-metal hydride clusters, some of which undergo dynamic incorporation of H – ion(s), have been reported, ,,, but they have commonly been synthesized from nonaqueous solution and are unstable in aqueous media. To our knowledge, this is the first {Ag 4 H} 3+ cluster species formed via the “empty” {Ag 4 } 4+ precursor through the insertion of a hydride ion, although {Ag 4 H} 3+ moieties have been found in {Ag n H m } ( n − m )+ clusters as subunits. A drastic color change from the dark red of [ 1 ] 8– to the yellow of [ 2 ] 9– , which is explained by the difference in the electronic states between {Ag 4 } 4+ and {Ag 4 H} 3+ , is also reported.…”
Section: Introductionmentioning
confidence: 92%